Manajemen Kesiswaan Ekstrakulikuler Content Creator Dalam Pengembangan Publikasi Digital Islami Di Smk Swadaya Semarang - Hatmojo, Rivaly Dhafin; Ahwan, Muh Ahlis (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to analyze student management in the extracurricular management of YouTube Content Creator and its contribution to the development of Islamic digital publications at SMK Swadaya Semarang. This study uses a descriptive qualitative approach with a case study type. The subjects of the study include the vice principal for student affairs, extracurricular coaches, and students who are members of the activity. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation. Data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawn, with validity testing through triangulation of sources and techniques. The results of the study show that extracurricular management has implemented an education management function that includes planning, organizing, implementing, and evaluating systematically. The program is designed based on learning outcomes and the division of tasks according to students' interests and competencies. The content production process is carried out through structured stages ranging from idea planning to publication and evaluation. Supervision is carried out not only on the technical aspect, but also on the integration of Islamic values in digital content. This activity has a positive impact on increasing digital literacy, creativity, confidence, student achievement, and strengthening the image of schools in the digital era. However, there are still obstacles in terms of discipline and commitment of members, so continuous evaluation is needed. This research shows that content creator-based extracurriculars can be an innovative model of student management in developing professional, educational, and characterful Islamic digital publications in vocational school environments. Keywords: : student management, extracurriculars, content creators, Islamic digital publications, digital literacy. Abstrak: : Penelitian ini bertujuan untuk menganalisis manajemen kesiswaan dalam pengelolaan ekstrakurikuler YouTube Content Creator serta kontribusinya terhadap pengembangan publikasi digital Islami di SMK Swadaya Semarang. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis studi kasus. Subjek penelitian meliputi wakil kepala sekolah bidang kesiswaan, pembina ekstrakurikuler, serta siswa anggota kegiatan. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi. Analisis data menggunakan model interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan, dengan uji keabsahan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa manajemen ekstrakurikuler telah menerapkan fungsi manajemen pendidikan yang meliputi perencanaan, pengorganisasian, pelaksanaan, dan evaluasi secara sistematis. Program dirancang berbasis capaian pembelajaran dan pembagian tugas sesuai minat serta kompetensi siswa. Proses produksi konten dilakukan melalui tahapan terstruktur mulai dari perencanaan ide hingga publikasi dan evaluasi. Pengawasan dilakukan tidak hanya pada aspek teknis, tetapi juga pada integrasi nilai-nilai Islami dalam konten digital. Kegiatan ini memberikan dampak positif terhadap peningkatan literasi digital, kreativitas, kepercayaan diri, prestasi siswa, serta penguatan citra sekolah di era digital. Meskipun demikian, masih terdapat kendala pada aspek kedisiplinan dan komitmen anggota sehingga diperlukan evaluasi berkelanjutan. Penelitian ini menunjukkan bahwa ekstrakurikuler berbasis content creator dapat menjadi model inovatif manajemen kesiswaan dalam mengembangkan publikasi digital Islami yang profesional, edukatif, dan berkarakter di lingkungan sekolah kejuruan. Kata kunci: manajemen kesiswaan, ekstrakurikuler, content creator, publikasi digital Islami, literasi digital.